Life cycle analysis of solar pv panels for their efiiciency, cost and environmental performance: a case study of hyderabad - Muhammad Saad Khan; Shah Nawaz Soomro; Wahaj Asif; Arsal Mehmood; Dr. Nayyar Hussain Mirjat; Dr. Zubair Ahmed Memon; Suhail Ahmed (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
As the demand of energy increases, renewable technologies are dominating in the recent years. Solar energy is one of the leading technologies in all of the renewable energies, due to its simplicity. In Pakistan, solar PV stand-alone units are mostly used to meet the energy requirements. During production of solar PV panel, it emits out lot of waste heat and it is necessary to calculate these emissions. This study investigates the complete Life Cycle Analysis (LCA) of two different types of solar panels which are locally available in Hyderabad markets. Complete modeling of Monocrystalline and Polycrystalline PV panels has been done by using GaBi software. This study shows the complete waste heat emissions during each stage of PV panel production. Two different types (Monocrystalline and Polycrystalline) of solar panels are designed under the dimensions of 1 m2. It is calculated that Monocrystalline PV panels are more efficient than Polycrystalline PV panels and they generates more units of electricity under same temperature conditions during its complete life. To enhance the electrical efficiency of solar PV panel, cooling system must be provided across it. The comparative analysis shows that Polycrystalline PV panels requires less amount of electrical energy as compare to Monocrystalline PV panels resulting in the reduction of waste heat emission. At the end of life, this study highlights the significance of recycling of solar panels which consider the reuse of the raw material. In this study, the combination of mechanical, thermal, and chemical process of recycling is considered. Recycling rate of solar PV panel has been assumed to be 90%. Recycling of raw material reduces the waste heat emission during purification process of raw material. Thus, cost is reduced and beneficial for environmental aspects. Result shows that recycling of solar PV panel is more beneficial than landfill for environmental and economic aspects.